Defining and Regulating Zero Hours Work: Lessons from a Liberal Market Economy - Ryan, Lorraine; Lavelle, Jonathan; O’Sullivan, Michelle; McMahon, Juliet; Murphy, Caroline; Turner, Tom; Gunnigle, Patrick; O’Brien, Mike (Nordic Journal of Working Life Studies, 2019)
The apparent rise in precarious work has received increased attention in a number of countries in recent decades. However, studies highlight the difficulties of both defining and capturing the extent of precarious work. In this paper, we report on a study of zero hours contracts in Ireland and drawing on the varieties of capitalism framework, examine the lessons for both LMEs and CMEs. The study found that zero hours contracts, as defined by Irish legislation, were not common; however, evidence of ‘If and When’ contracts emerged during the course of the research. We outline our key findings showing how information garnered from qualitative research provided nuanced insights on the reality of precarious work, which was not captured in the national data set. This is important for measuring the extent of precarious work in future studies.